Construir la República práctica: Estado, vías de comunicación e integración territorial en Ecuador, 1883-1895 (Estudios) - Medina, Alexis (2019)
This article focuses on the territorial integration policy promoted by progressive sectors between 1883 and 1895. Although there is a marked contrast between their ambitious infrastructure program and its tangible outcomes, the progressives contributed to expanding the State’s role in building public works in three ways. First, the State became the principal promoter of various railway projects connecting the coastal region with the sierra. In 1883, it also reestablished the Polytechnic University founded by García Moreno to train engineers Finally, it started establishing an institutional infrastructure focusing specifically on public works.